Estudo comparativo entre o Cu(INA)2-MOF e o complexo [Cu(INA)2(H2O)4] para reação click e de Biginelli e avaliação antifúngica dos compostos triazólicos - Willig, Julia Caroline Mansano (2020)
The catalytic activity of metal-organic framework Cu(INA)2 (INA = isonicotinate ion) and the complex [Cu(INA)2(H2O)4] were studied in the Copper-catalyzed Azide-Alkyne Cycloaddition (CuAAC) and Biginelli reactions under solvent-free reaction conditions. The robust, efficient and eco-friendly new method allowed the preparation of a variety of 1,2,3-triazole compounds in good to excellent yields and high selectivity for the 1,4-disubstituted triazole. In addition, it was possible to obtain triazoles containing the selenium atom that due to the molecular hybridization strategy present important biological activities. For the Biginelli reaction between aldehydes, ethyl acetoacetate and urea, the corresponding dihydropyrimidinones (DHPMs) also were obtained in satisfactory yields under mild reaction conditions for both catalysts. The comparative study between Cu(INA)2-MOF and [Cu(INA)2(H2O)4] complex demonstrated better results for the Cu-MOF, both for the yields and the regioselectivity of the products. Furthermore, no change in the heterogeneous catalyst structure was observed after the reaction, allowing them to be recovered and reused without any loss of activity. The 1,2,3-triazoles were evaluated for their antifungal activity against phytopathogenic fungi, and the compounds (3a, 3e, 3f, 3g, 3i, 3j, 3k) presented in this work showed significant activity providing an experimental basis for future studies of new fungicides.